Effects of millennium development goals and capacity building on social studies teachers’ competencies and students’ learning outcomes in social studies in Kogi State (2017)
Students 'performances in Junior Secondary School Social Studies in recent time have not been encouraging. Teachers also attributed woeful performances of students to poor staff development training. The study investigated the effects of Millennium Development Goals Capacity Building on Social Studies Teachers' Competencies and Student's Learning Outcome in Kogi State. This study is a descriptive research of survey type adopting multi-stage sampling technique. Data were collected from 40 Social Studies teachers and 360 JSSII students from 12 schools in Kogi State. Three research questions and three instruments guided the study with reliability coefficients of 0.68 for TCQ; 0.76 for CIS and 0.72 for SSAT. Data were analysed using descriptive statistics and Pearson Product Moment Correlation. Results revealed that relationship exists between MDGs' teachers ’competencies in classroom management and students' learning outcomes (r =0.30); positive significant relationship exists between MDGs teacher competencies and students' learning outcomes (r = 0.13) and larger percentage of the participants with MDGs capacity Building acquired more teaching skills in the course of the training. It is recommended that teachers should appropriate their newly acquired skills to increase students 'learning outcomes and be proactive in creating enabling environment in order to motivate students to learn.